2018
DOI: 10.3389/fonc.2018.00547
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism in Prostate Cancer; From Basic Science to New Therapeutic Strategies

Abstract: An increasing amount of research has recently strengthened the case for the existence of iron dysmetabolism in prostate cancer. It is characterized with a wide array of differential expression of iron-related proteins compared to normal cells. These proteins control iron entry, cellular iron distribution but also iron exit from prostate cells. Iron dysmetabolism is not an exclusive feature of prostate cancer cells, but it is observed in other cells of the tumor microenvironment. Disrupting the machinery that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 131 publications
2
18
0
Order By: Relevance
“…As a therapeutic strategy for cancer and CSCs, attention is recently focused on iron metabolism [35,36,37]. We confirmed some basic effects by iron chelator.…”
Section: Discussionsupporting
confidence: 73%
“…As a therapeutic strategy for cancer and CSCs, attention is recently focused on iron metabolism [35,36,37]. We confirmed some basic effects by iron chelator.…”
Section: Discussionsupporting
confidence: 73%
“…Beyond the tumorigenic potential of iron, tumor cells also exhibit a shift in iron homeostasis toward exacerbated intracellular iron sequestration through increasing uptake and storage, downmodulating export, or both mechanisms. This is evidenced by the downmodulation of FPN1 and overexpression of its natural inhibitor, hepcidin, in a variety of solid tumors, e.g., breast, ovarian, and prostate cancer [ 64 , 65 , 66 , 67 , 68 ]. When disturbed, the ferroportin–hepcidin axis indeed promotes breast-tumor growth mediated by BMP6- and IL-6-induced hepatic hepcidin, thus leading to an increase in the intracellular LIP [ 69 ].…”
Section: Iron Oxide-driven Biological Activities: Cellular Iron Mementioning
confidence: 99%
“…This has made it a desirable target for cancer treatment and prevention. 19 Previous studies have shown that iron metabolism may contribute to certain cancers, including lung cancer, 20 leukemia, 21 prostate cancer, 22 and kidney cancer. 23 However, the prognostic signature of iron metabolism in GC needs to be adequately explored.…”
Section: Discussionmentioning
confidence: 99%